2005
DOI: 10.1111/j.1601-0825.2005.01072.x
|View full text |Cite
|
Sign up to set email alerts
|

Klippel–Trenaunay syndrome

Abstract: Klippel-Trenaunay syndrome (KTS) is a congenital disorder characterized by triad of vascular nevi, venous varicosities and hyperplasia of soft and hard tissues in the affected area. This syndrome usually affects the extremities but occasionally can manifest in the craniofacial region, including the oral cavity. We report a case of KTS and discuss the oro-surgical and dental considerations regarding hemorrhagic tendencies caused by the known local anomalies such as vascular malformations associated with this sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…U re gi o ni ma za hva će nim hiper tro fi jom mo gu se ja vi ti he man gi o mi ko že (ne vus flam meus) raz li či te ve li či ne i ne pra vil nog ob li ka. Kao va sku lar ne le zije, u sklo pu ovog sin dro ma mo gu se ja vlja ti i va ri ko zi te ti [1][2][3][4][5]. Mo del na sle đi va nja KTVS ni je po znat, eti o lo gi ja ni je sa svim rasve tlje na, ali uzrok mo gu bi ti me zo der mal ne ano ma li je to kom em bri o nal nog raz vo ja.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…U re gi o ni ma za hva će nim hiper tro fi jom mo gu se ja vi ti he man gi o mi ko že (ne vus flam meus) raz li či te ve li či ne i ne pra vil nog ob li ka. Kao va sku lar ne le zije, u sklo pu ovog sin dro ma mo gu se ja vlja ti i va ri ko zi te ti [1][2][3][4][5]. Mo del na sle đi va nja KTVS ni je po znat, eti o lo gi ja ni je sa svim rasve tlje na, ali uzrok mo gu bi ti me zo der mal ne ano ma li je to kom em bri o nal nog raz vo ja.…”
Section: Discussionunclassified
“…Cutaneous hemangiomas (naevus flammeus) of varying extent and irregular contours are often present in the hypertrophic regions. Varicosities may also be part of the vascular lesions of this syndrome [1][2][3][4][5]. The pattern of inheritance for KTWS is unknown and its aetiology has not yet been determined, but it may be caused by mesodermal abnormalities during foetal development.…”
Section: Introductionmentioning
confidence: 99%
“…This syndrome usually affects the extremities but occasionally it may be manifested in the craniofacial region, including the oral cavity. 8 The association between extensive venous malformations and hypercoagulability is well established. Haematological evidence of low-grade consumptive coagulopathy has been documented repeatedly for patients with large venous malformations.…”
Section: Commentsmentioning
confidence: 99%
“…Klippel-Trenaunay syndrome (KTS, MIM *149 000) is a congenital vascular disease characterized by malformations of capillary vessels, veins, and lymphatics, and soft tissue or bony hypertrophy. 1–5 The cause of KTS is poorly understood, but our previous studies identified AGGF1 as the first gene associated with KTS and showed that KTS is caused by increased AGGF1 expression. 6…”
mentioning
confidence: 99%